Discounts for people with disabilities in Polish tourist attractions (Understanding Disability: Issues, Research, Reflections, 2021)
The Constitution of the Republic of Poland guarantees people with disabilities unrestricted access to cultural sites. In order to facilitate the exercise of this right, the Act on museums provides for a discount on admission tickets to state museum for people with disabilities and their guardians, while the Nature Protection Act specifies that people with disabilities have the right to a 50% discount on entrance tickets to national parks. The article analyses the system of discounts in most visited Polish tourist attractions in 2018 (with at least 200,000 visitors) in order to verify: 1) whether they are implemented in accordance with the law in national parks and state museums, 2) whether any discounts are provided for people with disabilities and/or their guardians in other types of facilities, 3) what the amount of the discount is. The analysis is followed by conclusions with conclusions and remarks regarding the law as it should stand.